Polymer solid-state battery electrolyte, solid-state lithium battery and method

By using polymer solid-state battery electrolytes containing specific groups in polymer lithium batteries and combining them with compound solid-state electrolytes, the temperature resistance, conductivity and interface compatibility problems of polymer lithium batteries are solved, and higher electrochemical performance and cycling stability are achieved.

CN119650836AActive Publication Date: 2025-03-18SHENZHEN MINGYU ENERGY CO LTD

Patent Information

Application Number
CN202411872803.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-18
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The polymer lithium battery has poor temperature resistance, compression resistance and deformation resistance, low conductivity, and poor compatibility between solid electrolyte and electrode, which has interface problems.

Method used

Polymer solid-state battery electrolytes containing alcohol groups, hydroxy groups, amine groups, halogen groups, sulfonic acid groups, acyl groups or dilute hydrocarbon materials are used, specifically including substances with the chemical formula (C13H14F3NO2)n or substances containing a specific molecular structure. The viscous polymer is formed by a specific preparation method and combined with the compound solid electrolyte to improve interface compatibility.

Benefits of technology

The conductivity and thermal stability of polymer solid-state battery electrolytes are improved, the compatibility and interface contact performance of electrodes and solid-state electrolytes are enhanced, and the electrochemical window and cycle stability is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650836A_ABST
    Figure CN119650836A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of polymer batteries, and particularly relates to a polymer solid-state battery electrolyte, a solid-state lithium battery and a method. The polymer solid-state battery electrolyte comprises one or more groups selected from an alcohol group, a hydroxyl group, an amine group, a halogenated group, a sulfonic acid group, an acyl group, a dilute hydrocarbon material and a carboxyl group, a film has high thermal stability, and the average coulombic efficiency of a battery of the polymer electrolyte is higher than 99%. The polymer solid-state battery electrolyte has high cycling stability, the membrane of the polymer solid-state battery electrolyte has good ionic conductivity, exchange and transmission of lithium ions are promoted, the high ionic conductivity of the membrane reflects good ion diffusion and migration ability of the membrane, and the membrane has a high electrochemical window; the membrane of the polymer solid-state battery electrolyte improves the contact or compatibility effect of an electrode and a solid-state electrolyte interface, and the membrane of the polymer solid-state battery electrolyte has profound significance in solid-state batteries and electrolytes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of olefin polymer batteries, and in particular to a polymer solid-state battery electrolyte, a solid-state lithium battery and a method. Background Art

[0002] Solid-state batteries and their electrolytes have high energy density and are safer. They can significantly reduce the amount of negative electrode materials used. They are thin and small in size, reducing the use of diaphragms and electrolytes in traditional batteries. The distance between the positive and negative electrodes of solid-state batteries can be shortened to even only a few to a dozen microns, and the thickness of the battery can be greatly reduced. The battery has the prospect of miniaturization, thin film and flexibility. Solid-state batteries are safer. Solid-state batteries are expected to solve the problem that lithium dendrites may appear in traditional lithium batteries and puncture the diaphragm to cause battery short circuits. Solid-state batteries are also expected to solve the problem that the electrolyte of traditional batteries is an organic liquid, which is prone to side reactions, oxidative decomposition, gas generation, and combustion tendency at high temperatures. In addition, a large number of valuable metal components in traditional electrolyte lithium batteries entering the environment will cause serious harm to humans and the environment. At the same time, lithium, cobalt, nickel and other metals are scarce metals with large demand. The problem of metal recycling and reuse in traditional electrolyte batteries is imminent. Therefore, finding recycling and environmentally friendly utilization of waste lithium batteries with high recycling efficiency and low economic cost is the right path for the green and sustainable development of lithium batteries.

[0003] Polymer solid-state batteries have many advantages such as high specific energy, miniaturization, ultra-thinness, light weight and high safety. Based on these advantages, lithium polymer batteries can be made into batteries of any shape and capacity to meet the needs of various products. However, the chemical properties of polymer lithium are very active, and the temperature inside the battery will continue to rise. Polymer electrolytes have the following defects: poor temperature resistance, pressure resistance, deformation resistance, poor conductivity, poor compatibility between solid electrolytes and electrodes, and interface problems with other solid electrolytes. Summary of the invention

[0004] In order to solve one of the above problems, the present application provides a polymer solid-state battery electrolyte, which contains one or more groups of alcohol group, hydroxyl group, amine group, halogenated group, sulfonic acid group, acyl group, olefinic hydrocarbon material or carboxyl group.

[0005] Preferably, in the polymer solid-state battery electrolyte, the rare-earth hydrocarbon material, the amine group, the halogenated group, and the carboxyl group are composed of a chemical formula of (C 13 H 14 F3NO2)n or a substance containing the following molecular structure formula I,

[0006]

[0007] Preferably, containing (C 13 H14 The invention discloses a method for preparing a substance comprising dissolving 1-(3,4-difluorophenyl)prop-2-ene-1-amine and (E)-4-fluorobut-2-enoic acid in an aqueous solution at a molar ratio of 1:1, adding ammonium persulfate and ammonium bisulfite, heating to react to form a viscous polymer, and drying the polymer to form a powder, which is recorded as powder A.

[0008] The present application also provides a method for preparing a polymer solid-state battery electrolyte. In the first step, at least a certain amount of the powder A is prepared into a viscous solution with deionized water, lithium carbonate is added, and the solution is heated until the pH value no longer decreases. In the second step, a film is coated and dried to form a polymer solid-state battery electrolyte, which is recorded as film a.

[0009] Furthermore, a method for preparing a polymer solid-state battery electrolyte also includes a process of adding a compound solid electrolyte before the second step.

[0010] Furthermore, the method for preparing a polymer solid-state battery electrolyte also includes a process of combining the membrane a with the surface of the compound solid-state electrolyte after the second step.

[0011] Furthermore, in the method for preparing a polymer solid-state battery electrolyte, the compound solid electrolyte is at least Li7La3Zr2O 12 、LiNi 0.8 Co 0.1 Mn 0.1 O2、Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.05 O 11.99 F 0.02 One or more of, preferably, the Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.05 O 11.99 F 0.02 The lithium battery selected in the preparation includes Li2CO3 produced by the lithium cobalt nickel recovery and extraction method, and the lithium carbonate in the polymer solid-state battery electrolyte is preferably the lithium carbonate prepared by the lithium cobalt nickel recovery and extraction method included in the lithium battery.

[0012] The present application also provides a method for using a polymer solid-state battery electrolyte membrane, wherein the membrane a is used in combination with a battery electrode, which is beneficial to the compatibility of the solid electrolyte and the electrode and / or beneficial to the interface contact performance between the electrode and the electrolyte.

[0013] The present application also provides a method for testing the compatibility and / or interfacial contact of the electrolyte and electrodes of a polymer solid-state battery electrolyte membrane. The first step is to use a stainless steel column with a circular contact surface diameter to horizontally press at least the membrane a, the comparison membrane, the compound solid electrolyte sheet, and the comparison solid electrolyte sheet to test the depth of the stainless steel column pressed into the above-mentioned membranes and sheets; the second step is to test the conductivity values ​​of the membrane a, the comparison membrane, the compound solid electrolyte sheet, and the comparison solid electrolyte sheet in turn, and analyze the compatibility improvement effect of the solid electrolyte and the electrode in combination with the conductivity value and the depth of the stainless steel column pressed into the above-mentioned membranes and sheets.

[0014] Furthermore, when the conductivity values ​​of membrane a, the comparison membrane, and the compound solid electrolyte sheet are within a certain order of magnitude, when the interface contact depth or area is large, the impedance is small, and the solid electrolyte with a larger interface contact depth or area has better compatibility with the electrode.

[0015] The present application also provides a polymer solid-state battery, comprising any one of the polymer solid-state battery electrolytes described above.

[0016] Beneficial effects of the present application: the polymer solid-state battery electrolyte of the present application has at least one of the following effects

[0017] The polymer solid-state battery electrolyte has high conductivity or good stability or is easy to combine with compound electrolytes or improves the interface effect between electrodes and solid electrolytes:

[0018] 1. The polymer solid-state battery electrolyte membrane a maintains a constant weight after 48 hours at 250 degrees, indicating that the membrane a has high thermal stability. Furthermore, the average coulombic efficiency of the polymer electrolyte battery is higher than 99%, and has high cycle stability.

[0019] 2. The membrane a of the polymer solid-state battery electrolyte has good ionic conductivity. Specifically, the substance containing structural formula I has amino groups, fluoride ions, carboxyl hydroxyl groups, polyfluoride ions and other groups arranged in sequence around the three-dimensional space, which promote the exchange and transmission of lithium ions. The higher conductivity of membrane a reflects the better ion diffusion and migration ability of membrane a. Further, the substance containing structural formula I makes membrane a have a higher electrochemical window.

[0020] 3. The membrane a of the polymer solid-state battery electrolyte improves the interface contact or compatibility between the electrode and the solid electrolyte.

[0021] 4. The polymer solid-state battery electrolyte is easy to combine with other electrolytes. The film a of the polymer solid-state battery electrolyte is combined with the surface of the compound solid electrolyte; further, the combination includes matching composite, such as the powder A of the polymer solid-state battery electrolyte and Li7La3Zr2O 12or LLZO powder compound matching composite to form a contrast film; further, the polymer solid battery electrolyte containing the substance of structural formula I has amine groups, fluoride ions, carboxyl groups and the like around the space stereoscopic structure that are beneficial to Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.05 O 11.99 F 0.02 The spatial structure of the compound and its lithium interaction or combination make it easier for the two to match and compound, resulting in a synergistic gain effect in the conductivity results. Furthermore, the substance containing structural formula I in the polymer solid-state battery electrolyte will Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.05 O 11.99 F 0.02 When the compound is branched into a network in a spatial manner similar to its structural formula I and then matched and compounded with a polymer solid-state battery electrolyte containing structural formula I, the two have similarities at least in spatial structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the test result diagram of the cobalt recovery control agent for this application;

[0023] Figure 2 This is the infrared spectrum test diagram of the solid electrolyte membrane a of the polymer solid-state battery;

[0024] Figure 3 The electron microscope images of compound solid electrolyte powder B and composite solid electrolyte membrane b;

[0025] Figure 4 This is the XRD test diagram of compound solid electrolyte powder B;

[0026] Figure 5 The disc b made of compound solid electrolyte powder B and the comparison disc impedance spectrum test diagram at room temperature. DETAILED DESCRIPTION

[0027] The invention discloses a method for recovering and extracting lithium, cobalt and nickel from lithium batteries. The first step is to recover and extract non-lithium valuable metals. In 100 ml of acid solution, 3-10% of solid powder raw materials containing lithium (preferably waste batteries containing lithium, nickel and cobalt) are added, the pH is adjusted to below 5, and the solution is stirred at room temperature until the content of nickel, cobalt and manganese ions in the solution no longer increases. 1-3 moles of ammonia water and ammonium ions (ammonium ions are preferably ammonium chloride, and the molar ratio of ammonia water and ammonium chloride is 2:1) are added to the solution, the molar ratio of ammonia water and ammonium ions is 1:1-3, the pH is controlled at 8-9, and the mixture is stirred at 30-70°C for 10-120 minutes. min, filter and collect the precipitate including the high-valent heavy metal ions, then add 0.1-0.3g of sodium hydroxide to the filtrate to filter and separate the precipitate containing cobalt, add 0.1-0.3g of sodium hydroxide to the filtrate to filter and separate the precipitate containing nickel, slowly add phosphoric acid to the filtrate, control the pH to 6-8, filter and separate the precipitate containing iron phosphate, take the filtrate sample with at least two same cuvettes (preferably 10mm), record them as the test sample cuvette and the comparison sample cuvette respectively, add the cobalt recovery control agent (add 0.005-0.02 % cobalt recovery control agent solution, preferably adding 0.02% of the solution 0.1-0.5ml), control the pH of the liquid in the test sample cuvette not to exceed 10, react for 30 minutes, and test the absorbance at 520 microns with a spectrophotometer. In parallel, control the pH of the liquid in the comparison sample cuvette not to exceed 3, react for 30 minutes, and test the absorbance at 520 microns with a spectrophotometer. When the difference between the absorbance of the test sample and the absorbance of the comparison sample is less than 0.25, it means that the cobalt content in the filtrate is less than 0.1%, and then perform the lithium recovery step. When the test sample absorbance is less than 0.1%, the cobalt content in the filtrate is less than 0.1%. When the difference between the absorbance of the sample and the absorbance of the control sample is greater than 0.25, it is necessary to repeat the steps before taking the filtrate sample until the difference between the absorbance of the test sample and the absorbance of the control sample in the filtrate is less than 0.25 (the same test result was obtained by replacing the cobalt recovery control agent with 5-Cl-PADAB with a cobalt recovery control dose of 1.25 times, so the cobalt recovery control agent can be replaced by 5-Cl-PADAB in the non-lithium valuable metal recovery and extraction step). The method of the present application recovers cobalt and nickel in sequence, and controls the return of cobalt to a filtrate content of less than 0.1%;

[0028] The second step is the lithium recovery step. 0.02-2% carbonic acid is added to the filtrate after the first valuable metal recovery and extraction step, heated and stirred to react until precipitation is filtered and separated including the remaining manganese. Then at least 0.02% carbonic acid is added to the filtrate to completely precipitate the lithium, and dried to obtain the finished lithium carbonate product.

[0029] The results of content analysis of the lithium carbonate obtained in the second step show that the mass percentage of calcium is less than 0.02%, the mass percentage of heavy metals in terms of lead is less than 0.001%, and other impurities are not lower than analytical pure lithium carbonate. Therefore, the lithium carbonate prepared in the present application is beneficial for use as a raw material for the preparation of lithium batteries or solid-state lithium batteries. Preferably, the lithium carbonate prepared as described above is used as a raw material for preparing polymer solid-state battery electrolytes or substances or compounds of structural formula I solid electrolytes.

[0030] Furthermore, the method also includes a third step: a step of separating and recycling the cobalt recovery control agent: collecting the sample solution added with the cobalt recovery control agent after the completion of the first step for multiple times (i.e., collecting the liquid added with the cobalt recovery control agent in the cuvette), preferably the sample solution collected during the industrial production process is not less than 3 kg, filtered with a (3 micron) filter paper, intercepting and separating the cobalt recovery control agent after the reaction, eluting the separated cobalt recovery control agent with an acid solution with a pH not exceeding 3 for multiple times, and testing the cobalt content in the eluent with a spectrophotometer, the test result shows that cobalt ions appear, continuing the elution test until the content of cobalt ions in the eluent no longer increases, and then drying and granulating the eluted cobalt recovery control agent and reusing it (the solution after the cobalt recovery control agent is burned again is tested for cobalt ions by atomic absorption, indicating that the cobalt recovery control agent can be regenerated with an acid solution with a pH not exceeding 3 after absorbing cobalt ions). This method is beneficial to resource recovery and reducing environmental pollution. In the third step, the 5-Cl-PADAB cannot be used to replace the cobalt recovery control agent. Further, the acid solution immersed in the lithium-containing solid raw material in the first step of the present invention can be the elution solution after the elution, and more preferably, the lithium-containing solid raw material is fully contacted and reacted with the acid solution in countercurrent to achieve countercurrent leaching of the metal in the lithium solid raw material. The method of the present invention is beneficial to the environmentally friendly recovery of valuable metals in waste batteries, the recovery process has low energy consumption, the amount of acid used for recovery is small, the recovery process is efficient and fast, the recovery method is easy to master, the impurity control of the recovered and extracted product is stable, it is beneficial to use it as a raw material for battery preparation, the recovery process is environmentally friendly and efficient, the hydrochloric acid involved in the above steps can also be the recovered hydrochloric acid involved in this application, and the pH of the raw material hydrochloric acid involved in this application cannot exceed 1.8.

[0031] The following describes the process of treating or recovering hydrochloric acid from the gas produced by the acid in the process of this application, including but not limited to the following schemes. The waste gas contains a small amount of partially absorbed HCl waste gas, which is collected and sucked into a storage tank. If these waste gases do not meet the emission standards through testing, when treating these waste gases that do not meet the emission requirements, since the hydrochloric acid waste gas treatment is water absorption and alkali absorption, generally when treating hydrochloric acid waste gas, when the concentration is high, water is absorbed into hydrochloric acid. The hydrochloric acid recovered from this waste gas can be reused. The reused hydrochloric acid is called recovered hydrochloric acid. If an unexpected situation occurs and it cannot be used, then in order to ensure that the emission meets the standards, alkali absorption is added. The above-mentioned absorbed water or alkali is the absorption liquid;

[0032] The absorption process can be treated by jet injection equipment, which is a device that uses high-speed jet flow energy to transport waste gas and absorption liquid. In the jet injection equipment, high-pressure liquid converts liquid energy into kinetic energy through a nozzle, thereby transporting the gas and liquid mixture to the next treatment device or system. In the treatment process of the jet pump, the waste gas first enters the jet injection equipment through one or more nozzles, where the high-pressure liquid mixes with the waste gas. The high-pressure liquid contains water absorption liquid. The hydrogen chloride in the waste gas can easily combine with the absorption liquid to form hydrochloric acid, and the high-speed flow energy of the liquid is used to absorb the harmful substances in the waste gas. Then the gas and liquid mixture enters the diffuser, converting kinetic energy into pressure energy, thereby achieving further treatment of the waste gas. After the injection treatment, the HCl gas content in the waste gas can be recycled or reduced to meet the requirements of emission standards.

[0033] The present application also provides a method for preparing a cobalt recovery control agent

[0034] Add 0.5 mol 5-Cl-PADAB to a three-necked flask containing 50 ml of methanol solution, then add 0.8 mol (1-chlorovinyl) cyclopropane, stir at 0-25°C for 3 hours, keep warm at 30°C for 3 hours, place at 35°C with frequent stirring for 12 hours, heat and filter to separate the methanol solution, and obtain C 16 H 16 ClN5, C 16 H 16 ClN5 is added to methanol to prepare a 30% solution, and 0.05 mass of azobisisobutyronitrile is added to the solution and heated. Nitrogen is introduced and heated to react until the solution becomes viscous. After the molecular weight is tested to be not less than 1 million, granulation and drying are passed through infrared spectrum test. The test results of cobalt recovery control agent are as follows Figure 1 ,Depend on Figure 1It can be seen that the characteristic absorption of chlorine-containing groups is at 600-700cm-1 and 1000-1300cm-1, azobenzene is at 1570-1550cm-1 and 323cm-1, the absorption peak of pyridine molecules is at 1580cm-1, and there is no large absorption wave of olefins at 2930cm-1 and 2850cm-1, indicating that the double chemical bond is open, the absorption wavelength of diamine is at 3500-3150cm-1 and 1350-1100cm-1, and cyclopropane is at 3310-3000cm-1 in infrared light. From the above analysis, it can be seen that the formation of a molecule with the molecular formula [C 16 H 16 ClN5]n or a substance containing the following structural formula II,

[0035]

[0036] Use [C 16 H 16 ClN5]n replaces 5-Cl-PADAB in the cobalt reagent spectrophotometry method in GB / T 4325.8-2013 to test alloy steel containing 0.05% cobalt. 16 H 16 The same effect was obtained by using 80% of 5-Cl-PADAB in the ClN5]n test, and the repeatability limit of the test results was 0.0007%. The analytical task was at least due to the presence of diamine and cyclopropane structures. 16 H 16 The ClN5]n test of alloy steel containing 0.05% cobalt can achieve the repeatability of the test results in the shortest time than the 5-Cl-PADAB test under the same conditions. In addition, the test results of other cobalt-containing liquids can also be used. 16 H 16 ClN5]n replaces 5-Cl-PADAB, but uses the [C 16 H 16 ClN5]n was prepared into an aqueous solution less than 30% by mass and filtered with filter paper with a pore size less than 5 microns. All the [C 16 H 16 ClN5]n is retained on the filter paper, while under the same conditions, the 5-Cl-PADAB can all pass through the filter paper with a pore size of less than 5 microns.

[0037] A polymer solid-state battery electrolyte of the present application is described below, wherein the polymer solid-state battery electrolyte comprises one or more groups of alcohol groups, hydroxyl groups, amine groups, halogenated groups, sulfonic acid groups, acyl groups, olefinic hydrocarbon materials, or carboxyl groups.

[0038] In one embodiment of the present application, the olefinic hydrocarbon material, the amine-containing group, the halogenated group, and the carboxyl group are composed of a chemical formula of (C13 H 14 F3NO2)n or a substance containing the following molecular structure I

[0039]

[0040] Contains (C 13 H 14 The invention discloses a method for preparing a substance comprising: dissolving 15 g of 1-(3,4-difluorophenyl)prop-2-ene-1-amine and (E)-4-fluorobut-2-enoic acid in a molar ratio of 1:1 in 100 g of an aqueous solution, adding 0.5% ammonium sulfate and 0.5% ammonium bisulfite, heating to react at 30-60°C for not less than 6 hours to form a viscous polymer, granulating, drying and grinding the polymer into powder, which is recorded as powder A. The powder A contains a substance of the following molecular formula I.

[0041] A method for preparing a polymer solid-state battery electrolyte comprises: preparing a certain amount of powder A with deionized water into a solution with a viscosity not exceeding 10 mPa.s, preferably testing the viscosity with a digital six-speed rotary viscometer, adding lithium carbonate according to a mass ratio (A: lithium carbonate mass ratio is 30:1), heating to 60 degrees and stirring until the pH of the solution no longer decreases, coating with a flat surface dish and drying, the coating thickness not exceeding 1 cm, preferably 1 mm, and cutting with a cutting machine into 12 mm discs, which are recorded as film a, that is, film a belongs to a type of polymer solid-state battery electrolyte;

[0042] The membrane a was kept at a constant weight at 250 degrees for 48 hours in a constant temperature drying oven, indicating that the membrane a has high thermal stability. The lithium carbonate is preferably lithium carbonate prepared in the lithium cobalt nickel recovery and extraction method in the lithium battery. In addition, the above 1-(3,4-difluorophenyl)prop-2-ene-1-amine can be replaced by 2,2,2-trifluoroethyl acrylate, and the (E)-4-fluorobut-2-enoic acid can also be replaced by (E)-4,4,4-trifluorobut-2-enoic acid.

[0043] The infrared spectrum test results of the polymer solid-state battery electrolyte on membrane a are as follows Figure 2 ,Depend on Figure 2 It can be seen that the characteristic absorption of fluorine groups and benzene groups appears at 2930, 2700, 1590, 1410, 1080, 790, 770 cm-1, etc., the amine group appears at about 1500 cm-1, the hydroxyl peak appears at 1600 cm-1, and there is no obvious olefin C=C stretching vibration at 1640 cm-1. It can be seen that the powder A contains the substance with the following molecular structure I

[0044]

[0045] The above-mentioned method for preparing a polymer solid-state battery electrolyte further includes a process of adding a compound solid electrolyte before the second step; after the second step, it also includes a process of combining membrane a with the surface of the compound solid electrolyte (in a non-gel state), and the combination of membrane a and the surface of the compound solid electrolyte belongs to a type of polymer solid electrolyte; membrane a or the combination of membrane a and the surface of the compound solid electrolyte also belongs to the matching composite one in the combination.

[0046] A certain amount of powder A was prepared into a solution with a viscosity not exceeding 10 mpa.s with deionized water, lithium carbonate was added according to the mass ratio (A: lithium carbonate mass ratio is 30:1), heated to 60 degrees and stirred until the pH of the solution no longer decreased, and then Li7La3Zr2O was added according to the mass ratio. 12 Or LLZO powder is stirred to form a uniform gel (powder A: Li7La3Zr2O 12 Or the mass ratio of LLZO powder is 1-4:5-6, Li7La3Zr2O 12 Or LLZO powder (referred to as comparative powder, purchased on the current market), coated with a flat surface dish and dried, the coating thickness does not exceed 1.3mm, preferably 1mm, cut into 12mm discs with a cutting machine and recorded as comparative film, the comparative film belongs to Li7La3Zr2O 12 Or the compound of LLZO powder and the powder A of polymer solid-state battery electrolyte are matched and compounded.

[0047] The following describes a solid-state battery compound solid electrolyte of the present application, the compound having a general formula of: AwBxCyDz wherein A comprises one or more of Li, Na, K, Ca, Mg, Fe, Cu, V, and Cr, B comprises one or more of La, Sr, Y, Ba, Ga, Bi, Ce, Sm, Pr, Nd, Al, Ni, and Co, C comprises one or more of Zr, Nb, Ti, Ta, Mo, Rh, Ir, Pt, Sb, Sc, Zn, Ru, W, Mn, Si, and P, and D comprises one or more of F, Cl, Br, I, O, and S, wherein 1≤w ≤8,0≤x≤5,0≤y≤4,0≤z≤15, (when any one of A or B or C or D is composed of multiple elements, the corresponding number of w, x, y, and z is the algebraic sum of the multiple constituent elements, and each element in A is preferably a substance whose common valence ranges from 1 to 2.9, each element in B is preferably a substance whose common valence is greater than 2, each element in C is preferably a substance whose common valence is not less than 4, and each element in D is preferably a substance whose common valence is not greater than -2); the solid-state battery solid electrolyte of the present application has far-reaching significance in the field of solid-state batteries as a lithium-ion battery monomer.

[0048] A specific implementation of a solid-state battery compound solid electrolyte is described below.

[0049] The compound includes Li7La3Zr2O 12 、LiNi 0.8 Co 0.1 Mn 0.1 O2, Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.05 O 11.99 F 0.02 One or more of the compounds.

[0050] An embodiment of a solid-state battery compound solid electrolyte, containing Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.9 5Si 0.05 O 11.99 F 0.02 Preparation of the compound: Li2CO3, K2O, Na2O, Al(OH)3, La(NO3)3·6H2O, Zr(NO3)4, C8H 21 NSi (butyldimethyl (dimethylamino) silane), (C 13 H 14 A total of 3 moles of F3NO2)n are stirred and added to deionized water in sequence, and the pH value is adjusted to 5-7 to form a solution. After heating to 30-45, ultrasonic stirring is preferably performed for 1-5 hours to form a gel. After granulation, it is blown and dried at 100°C. After being crushed into powder, the powder is placed in an alumina crucible and placed in a muffle furnace. The temperature is raised to 1000-1200°C at a rate of 2°C / min, and the temperature is kept for 1-6 hours and then cooled with the furnace. The sintered powder is placed in a ball mill, isopropyl ketone is added, and ball milled at a speed of 600r / min for 10 hours. The powder obtained after ball milling (preferably about 300 meshes) is recorded as powder B. After vacuum drying in a vacuum drying oven for 6 hours, the pre-used powder is formed and placed in a dryer for storage. In addition, the Li2CO3 preferably includes lithium carbonate prepared in the lithium cobalt nickel recovery and extraction method in the lithium battery, and the lithium cobalt nickel recovery and extraction method also provides a suitable raw material for the preparation of compound solid electrolytes;

[0051] Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si0.05 O 11.99 F 0.02 The preparation of the compound (C 13 H 14 F3NO2)n is powder A, and non-lithium-containing (C 13 H 14 F3NO2)n participates in the reaction to prevent (C 13 H 14 The hydroxyl group, amine group, etc. in F3NO2)n affect the lithium complex adsorption and the lithium content in the compound or the structural shape of the compound; further, the (C 13 H 14 F3NO2)n or powder A has a branched network shape Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.05 O 11.99 F 0.02 Effects of compounds.

[0052] The preparation method of membrane b or a composite solid-state battery electrolyte is as follows:

[0053] A certain amount of powder A is prepared into a solution with a viscosity not exceeding 10mpa.s with deionized water, lithium carbonate is added according to the mass ratio (A: lithium carbonate is 30:1, and the use of lithium-containing powder A is beneficial to the contact sites and migration of lithium), heated to 60 degrees and stirred until the pH of the solution no longer decreases, and then powder B is added according to the mass ratio and stirred to form a uniform gel (A: powder B mass ratio is 1-4:5-6), and a film is coated with a flat surface dish and dried. The coating thickness does not exceed 1.3mm, preferably 1mm, and is cut into 12mm discs with a cutting machine and recorded as film b. Film b also realizes the branched network containing Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.05 O 11.99 F 0.02 Compound powder B and polymer solid-state battery electrolyte powder A are matched and composited, and membrane b belongs to another matched composite in the combination, and membrane b also belongs to a composite solid electrolyte.

[0054] The following parameter performance tests are conducted on compound solid electrolyte powder B and composite solid electrolyte membrane b. Figure 3 The electron microscope images of compound solid electrolyte powder B and composite solid electrolyte membrane b are shown in Figure 2. Figure 3 (B) is an electron microscope image of solid electrolyte powder B. Figure 3In (B), we can see a branched mesh-like shape (the arrow indicates the appearance of a mesh and short line prints). Figure 3 (b) is an electron microscope image of the composite solid electrolyte membrane b. From (b), we can see that the branched mesh-like fragments are cross-paved with wire mesh polymers, indicating a combination of polymer and compound (the circle indicates the shadow of the polymer electron microscope micrometer image / the arrow indicates the branched mesh fragment micrometer shadow). The polymer solid-state battery electrolyte part models the compound branched network and then compounds it with the polymer solid-state battery electrolyte.

[0055] The powder B material was subjected to elemental analysis by ICP combined with XPS, and the concentration content data of each element was processed by software and the percentage of each element was obtained as shown in Table 1.

[0056] Table 1

[0057] element Li Na K Al La Zr Si O F % 26.3 0.33 1.67 0.16 12.53 8.14 0.20 50.10 0.083

[0058] Figure 4 This is the spectrum of XRD test of compound solid electrolyte powder B. Figure 4 In the middle, powder B and Li7La3Zr2O 12 The standard card (PDF#40-0894 or PDF#45-0109) matches perfectly. In addition, the following analysis shows that: at 2θ of about 19°, 31°, and 38°, it is potassium-containing prismatic crystals, at 2θ of about 33.48°, 43.29°, etc., sodium prismatic crystals appear at 2θ of 38.4°, 44.5°, etc., aluminum prismatic crystals appear at 2θ of 21°, 27.5°, etc., which should be silicon-containing crystals, and fluorine-containing crystals appear at about 2θ of 10.9°, 18.8°, and 24.9°. Combined with the ICP element analysis of powder B material, it is believed that powder B is Na, K, Al, Si, O, and F modified Li7La3Zr2O 12 The complex compound or electrolyte formed by the crystal is denoted as Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.05 O 11.99 F 0.02 Compound.

[0059] Furthermore, this test also provides a tablet preparation method, by making electrolyte discs for relevant performance tests, powder B is selected as the implementation method: 0.1g powder B (pre-used powder) is weighed and placed in a stainless steel mold (diameter 12mm), and pressed at a pressure of 10-200MPa for 3min, with a thickness not exceeding 1cm or mm. The pre-pressed disc is recorded as disc b. The measurement meets the requirements, indicating that the compound solid electrolyte disc b is easy to make a suitable film. After the surface is treated, it is placed in a vacuum drying oven for storage.

[0060] The Li7La3Zr2O 12 Or LLZO powder (referred to as control powder), the discs prepared by the above tableting steps are referred to as control discs;

[0061] Furthermore, the combination or the matching combination in the combination can also press the membrane a on the two side surfaces of the wafer b to form membrane ab, and press the membrane a on the two side surfaces of the comparison wafer to form comparison membrane ab. This combination also belongs to the process of combining membrane a with the surface of the compound solid electrolyte.

[0062] The above-mentioned membrane a, membrane b, comparison membrane, disc b, comparison disc, membrane ab, and comparison membrane ab were placed flat between two stainless steel sheets with a diameter of 12 mm as electrolytes to form a stainless steel / electrolyte / stainless steel battery chemical test. The ionic conductivity, electrochemical window and other parameters of the electrolyte (4.43) were tested using an analyzer chemical workstation or the like using the AC impedance method. The battery temperature was controlled to room temperature or stable using a constant temperature oven. The test results are shown in Table 2 below.

[0063] Table 2

[0064]

[0065]

[0066] The impedance spectrum of the disc b made of compound solid electrolyte powder B and the comparison disc was tested at room temperature. Figure 5 The impedance spectrum test results of the disc b made of compound solid electrolyte powder B and the comparison disc at room temperature are shown in the figure. Figure 5 As shown, compared with the comparison disc, the compound solid electrolyte disc b has a higher conductivity. Furthermore, the small arc appearing in the compound solid electrolyte disc b reflects the Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.05 O 11.99 F 0.02 The compound material has good ion diffusion and migration capabilities. At least the modification and doping of Na, K, Al, Si, O, and F have certain beneficial effects on the material.

[0067] From the test results in Table 2, it can be seen that membrane a has good ion conductivity, indicating that the substance containing structural formula I has amino groups, fluoride ions, carboxyl hydroxyl groups, polyfluoride ions and other groups arranged in sequence around the three-dimensional space, which promote the exchange and transmission of lithium ions. The higher conductivity of membrane a reflects the better ion diffusion and migration ability of membrane a, and the substance containing structural formula I makes membrane a have a higher electrochemical window.

[0068] Combined with the above performance test results, the combination includes a compound and a polymer solid-state battery electrolyte, and a polymer solid-state battery electrolyte is formed into a branched network and then matched and composited. Specifically, the matching composite includes a branched network containing Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.05 O 11.99 F 0.02 Compound powder and polymer solid-state battery electrolyte powder are matched to form a composite film, that is, for Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.05 O 11.99 F 0.02 The matching composite effect and principle analysis of the compound powder and the polymer solid-state battery electrolyte powder containing the substance of structural formula I are as follows:

[0069] Film b is composed of Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.05 O 11.99 F 0.02 The conductivity of the composite method of the compound powder and the polymer solid-state battery electrolyte powder containing the substance of structural formula I is higher than the sum of the conductivity of the membrane a and the disc b, indicating that the Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.05 O 11.99 F 0.02 The compound powder and the polymer solid-state battery electrolyte powder containing the substance of structural formula I show a synergistic gain effect in conductivity, and the effect is significantly better than the comparative membrane. The comparative membrane uses a matching composite of membrane a and a comparative disc. As a result, the comparative membrane does not have an effect of conductivity higher than the sum of the two, and no synergistic gain effect occurs. Combined with electron microscopy, Figure 3It can be seen that the polymer solid-state battery electrolyte is a compound branched network modeling and then matched and compounded. Analysis shows that the substance containing structural formula I in the polymer solid-state battery electrolyte will Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.05 O 11.99 F 0.02 When the compound is branched into a network in a spatial shape similar to its structural formula I and then matched with a polymer solid-state battery electrolyte containing structural formula I, the two have similarities at least in spatial structure. Further, it is believed that the substance of structural formula I has amine groups, fluoride ions, carboxyl groups, etc. around the spatial stereo structure, which are beneficial to Li 6.4 Na 0.08 K 0.4 Al 0.0 4La3Zr 1.95 Si 0.05 O 11.99 F 0.02 The spatial structure of the compound and its interaction or combination with lithium make it easier for the two to match in a composite combination, resulting in a synergistic gain effect in the conductivity results.

[0070] The membrane a improves the interface effect between the electrode and the solid electrolyte or the combination of membrane a and the compound solid electrolyte interface, or the beneficial effect analysis is as follows:

[0071] A 50g stainless steel column with a contact surface diameter of 5mm was pressed horizontally on the membrane a, membrane b, comparison membrane, disc b, and comparison disc, and the depths of the stainless steel column into the above-mentioned membranes and discs were measured to be 0.6mm, 0.3mm, 0.2mm, 0.1mm, and 0.03mm, respectively. It can be seen that the interface integration or tolerance of the above-mentioned membranes and discs decreases in turn, and the integration or tolerance of all membranes is better than that of the discs. The conductivity values ​​of all membranes are also 10 -4 orders of magnitude, so combined with the test results of the conductivity in Table 1, it can be seen that the interface contact depth or area of ​​the comparison membrane, membrane b, and membrane a is successively larger and the impedance is smaller. It is analyzed that the compatibility of the corresponding solid electrolytes and electrodes of the comparison membrane, membrane b, and membrane a is better than that of the disc. The compound solid electrolyte disc b has a soft branched network structure. The disc b appears 0.1mm pressed into a certain depth. The analysis believes that its branched network structure is caused by elastic contraction. Therefore, membrane a, membrane b, and comparison membrane can be beneficial to the compatibility of solid electrolytes and electrodes and improve interface contact problems. Membrane ab and comparison membrane ab are a matching composite combination between membrane a and the surface of compound solid electrolyte. From the test results of their conductivity combined with electron microscopy Figure 3It can be seen that the surface structure is also a reflection of the effect of membrane a in improving the contact or compatibility between the electrode and the solid electrolyte. The above process also includes a method for using membrane a to test the compatibility of the electrolyte and the electrode and / or the improvement of the interface contact performance. The method of the membrane of the present application for testing the compatibility and / or interface contact of the electrolyte and the electrode is efficient, fast, easy to operate, and can also be used in solid-state battery assembly. The solid-state battery of the present application includes at least one combination of polymer solid-state battery electrolyte or solid-state battery compound solid-state electrolyte, such as selecting membrane a and electrode to form a polymer solid-state battery, or selecting membrane a, wafer b and electrode to form a composite or compound solid-state battery, or using membrane b and electrode to form a compound or composite solid-state battery.

[0072] Chemical tests on stainless steel / electrolyte / stainless steel batteries using membrane a, membrane b, comparison membrane, wafer b, membrane ab, and comparison membrane ab as electrolytes showed that after 400 cycles, they still had a discharge capacity of 130 mAhg-1, and the average coulombic efficiency of the battery was higher than 99%. The above membranes and wafers had high cycle stability.

[0073] Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.05 O 11.99 F 0.02 The presence of silicon in the compound is beneficial to structural stability and long-term circulation, F is beneficial to the surface performance and ion activity of the compound, which is beneficial to conductivity, and the coordination of Na, K, Al, and Si including large and small radii is beneficial to lithium ion migration, making the compound show a higher conductivity among the above test values.

Claims

1. A polymer solid-state battery electrolyte, characterized in that: The polymer solid-state battery electrolyte comprises one or more groups of alcohol groups, hydroxyl groups, amine groups, halogenated groups, sulfonic acid groups, acyl groups, olefinic hydrocarbon materials or carboxyl groups.

2. A polymer solid-state battery electrolyte as claimed in claim 1, characterized in that: The olefin material, amine group, halogenated group and carboxyl group are composed of the chemical formula (C 13 H 14 F3NO2)n or a substance containing the following molecular structure formula I, 3. A polymer solid-state battery electrolyte as claimed in claim 2, characterized in that: Contains (C 13 H 14 The invention discloses a method for preparing a substance comprising dissolving 1-(3,4-difluorophenyl)prop-2-ene-1-amine and (E)-4-fluorobut-2-enoic acid in an aqueous solution at a molar ratio of 1:1, adding ammonium persulfate and ammonium bisulfite, heating to react to form a viscous polymer, and drying the polymer to form a powder, which is recorded as powder A.

4. A method for preparing a polymer solid-state battery electrolyte, characterized in that: In the first step, at least a certain amount of the powder A is prepared into a viscosity solution with deionized water, lithium carbonate is added, and the solution is heated until the pH value no longer decreases. In the second step, the solution is coated and dried to form a polymer solid-state battery electrolyte, which is referred to as membrane a.

5. A method for preparing a polymer solid-state battery electrolyte according to claim 4, characterized in that: Before the second step, a compound solid electrolyte process is also included.

6. A method for preparing a polymer solid-state battery electrolyte according to claim 4, characterized in that After the second step, the process of combining the membrane a with the compound solid electrolyte surface is also included.

7. A method for preparing a polymer solid-state battery electrolyte according to any one of claims 4 to 6, characterized in that: The compound solid electrolyte is at least Li7La3Zr2O 12 、LiNi 0.8 Co 0.1 Mn 0.1 O2、Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.05 O 11.99 F 0.02 One or more of, preferably, the Li 6.4 Na 0.08 K 0.4 Al 0.04 Ln3Z 1.95 Si 0.0 5O 11.99 F 0.02 The lithium battery selected in the preparation includes Li2CO3 produced by the lithium cobalt nickel recovery and extraction method, and the lithium carbonate in the polymer solid-state battery electrolyte is preferably the lithium carbonate prepared by the lithium cobalt nickel recovery and extraction method included in the lithium battery.

8. A method for using a polymer solid-state battery electrolyte membrane, characterized in that: The use of membrane a in combination with a battery electrode is beneficial to the compatibility of the solid electrolyte with the electrode and / or to the interface contact performance between the electrode and the electrolyte.

9. A method for testing the compatibility and / or interfacial contact between an electrolyte and an electrode using a membrane prepared using a polymer solid-state battery electrolyte. The first step is to use a stainless steel column with a circular contact surface diameter to horizontally press at least the membrane a, a comparison membrane, a compound solid electrolyte sheet, and a comparison solid electrolyte sheet to test the depth of the stainless steel column being pressed into the above-mentioned membranes and sheets; the second step is to test the conductivity values ​​of the membrane a, the comparison membrane, the compound solid electrolyte sheet, and the comparison solid electrolyte sheet in turn, and analyze the effect of improving the compatibility between the solid electrolyte and the electrode in combination with the conductivity values ​​and the depth of the stainless steel column being pressed into the above-mentioned membranes and sheets.

10. A polymer solid-state battery, further characterized in that it comprises a polymer solid-state battery electrolyte as described in any one of claims 1-9.

Citation Information

Patent Citations

  • Inorganic-organic composite electrolyte membrane, preparation method therefor, and application thereof

    WO2023028900A1

  • Preparation and use of polymer-based composite solid-state electrolyte having high ionic conductivity

    WO2024139656A1

Cited By

  • Extraction liquid for extracting electrolyte in battery and extraction method

    CN120586442A